BENTUK PENYELESAIAN YANG TEPAT TERKAIT WANPRESTASI DEVELOPER ATAS BANGUNAN PRE PROJECT SELLING - Giatmokoputri, Aura Imtiyaz Qatrunnada; Taupiqqurrahman, Taupiqqurrahman (Kertha Semaya : Journal Ilmu Hukum, 2024)
The purpose of this study is to investigate the appropriate resolution method for defaults in Pre Project Selling projects and to comprehend the legal ramifications for developers who fail to honor contracts. Additionally, this research aims to elucidate the compensation regulations pertaining to breach of contract and evaluate the efficacy of PKPU (Postponement of Debt Payment Obligations) in safeguarding creditor rights. The study employs a normative legal research methodology, using statute approach, conceptual approach, and analytical approach. The findings suggest that consumers should pursue breach of contract claims through the judicial system, seeking the annulment of the Sale and Purchase Agreement (PPJB) along with compensation for expenses, losses, and interest. The effectiveness of PKPU in resolving Pre Project Selling projects remains uncertain, as non-compliance may result in bankruptcy, as indicated in the Homologation decision. Consequently, this places consumers at a disadvantage, as their status as concurrent creditors is not given priority. Keywords: Breach of Contract, Postponement of Debt Payment Obligations, Pre Project Selling